IbM KELOMPOK GUIDE LAWANG SEWU SEMARANG - Dodi Mulyadi; Testiana Deni Wijayatiningsih; Didik Sumanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
The quality of English speaking for  tour guides in Lawang Sewu need to improve in line with the globalization of tourism in Central Java that is being launched to bring a lot of tourists from within the country and abroad are known by the slogan “Visit Jateng 2013”. In accordance with this statement, we did “Pengabdian Masyarakat” dedicated servant of the community for group of guides of Lawang Sewu . the group was divided into two associations and community i.e. paguyuban siang and paguyuban sore. So far, the problems faced by your group Lawang Sewu is how to improve their English language skills with practical, efficient, and does not complicate the psychological learning and motivate them to be ready to serve foreign tourists.  The priority issues of partners (mitra)are how to improve English language skills of Lawang Sewu guides of Semarang, the absence of a practical and efficient guide to practice speaking and storytelling in English for your group Lawang Sewu Semarang, and the realization of the increase in the English language in guide of Lawang Sewu Semarang with appropriatemethods and interesting.  Targets and outcomes of science and technology activities (IPTEKS) for the community of quide in Lawang Sewu Semarang namely; increasing mastery of the English language for guide in Lawang Semarang with Drill method and Repetition, certificates for the guide, English guide to savings, increased motivation and psychological cont ol if travelers face bothdomestically and abroad so as to become a professional guide, and CD of English instruction to guide the improvement of the English language.  The solution offered in our devotion is to increase English skills of guides in Lawang Sewu Semarang, producing methods, materials, methods, and guidelines that are effective, and realize an increasing in their English skills. Therefore, Lawang Sewu is expected to become a symbol of quality foreign tourism by having a guide that is fluent in English.